Carbene metal amide photoemitters: tailoring conformationally flexible amides for full color range emissions including white-emitting OLED. Issue 2 (22nd November 2019) - Romanov, Alexander S.; Jones, Saul T. E.; Gu, Qinying; Conaghan, Patrick J.; Drummond, Bluebell H.; Feng, Jiale; Chotard, Florian; Buizza, Leonardo; Foley, Morgan; Linnolahti, Mikko; Credgington, Dan; Bochmann, Manfred
Abstract : Conformationally flexible "Carbene–Metal–Amide" (CMA) complexes of copper and gold show photoemissions across the visible spectrum, including mechanochromic behavior which led to the first CMA-based white light-emitting OLED. Abstract : Conformationally flexible "Carbene–Metal–Amide" (CMA) complexes of copper and gold have been developed based on a combination of sterically hindered cyclic (alkyl)(amino)carbene (CAAC) and 6- and 7-ring heterocyclic amide ligands. These complexes show photoemissions across the visible spectrum with PL quantum yields of up to 89% in solution and 83% in host-guest films. Single crystal X-ray diffraction and photoluminescence (PL) studies combined with DFT calculations indicate the important role of ring structure and conformational flexibility of the amide ligands. Time-resolved PL shows efficient delayed emission with sub-microsecond to microsecond excited state lifetimes at room temperature, with radiative rates exceeding 10 6 s −1 . Yellow organic light-emitting diodes (OLEDs) based on a 7-ring gold amide were fabricated by thermal vapor deposition, while the sky-blue to warm-white mechanochromic behavior of the gold phenothiazine-5, 5-dioxide complex enabled fabrication of the first CMA-based white light-emitting OLED.